2015
DOI: 10.5812/ijp.25(3)2015.198
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Evaluation of Myocardial Systolic Dysfunction in the Early Stage of Kawasaki Disease: A Speckle-Tracking Echocardiography Study

Abstract: Background:Evaluation of myocardial function by speckle-tracking echocardiography is a new method for the early diagnosis of systolic dysfunction.Objectives:We aimed to determine myocardial speckle-tracking echocardiography indices in Kawasaki Disease (KD) patients and compare them with the same indices in control subjects.Patients and Methods:Thirty-two patients (65.5% males) with KD and 19 control subjects with normal echocardiography participated in this study. After their demographic characteristics and cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 12 publications
2
9
0
Order By: Relevance
“…Kawasaki disease is a well-known, self-limited, systemic inflammatory vasculitis that mainly affects small-and mediumsized arteries. Several previous studies confirmed impaired left ventricular myocardial strain of KD in the acute phase using STE (20,22) or velocity vector imaging (25,26). Our results found that KD had impaired GLS and GCS in the acute phase compared with the healthy children, consistent with those published articles (20,22,25,26).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Kawasaki disease is a well-known, self-limited, systemic inflammatory vasculitis that mainly affects small-and mediumsized arteries. Several previous studies confirmed impaired left ventricular myocardial strain of KD in the acute phase using STE (20,22) or velocity vector imaging (25,26). Our results found that KD had impaired GLS and GCS in the acute phase compared with the healthy children, consistent with those published articles (20,22,25,26).…”
Section: Discussionsupporting
confidence: 92%
“…Several previous studies confirmed impaired left ventricular myocardial strain of KD in the acute phase using STE (20,22) or velocity vector imaging (25,26). Our results found that KD had impaired GLS and GCS in the acute phase compared with the healthy children, consistent with those published articles (20,22,25,26). The progressive structural alterations of the myocardium and coronary arteries were confirmed during the convalescent phase of KD in the previous studies (27)(28)(29).…”
Section: Discussionsupporting
confidence: 91%
“…Ventricular strain and torsion analysis by STE consist of capturing and tracking points of the two-dimensional echocardiogram throughout the cardiac cycle, generating movement vectors and strain. It has provided additional insight into the changes in systolic function in patients with PH by showing significant reductions in systolic torsion as well as LS and CS [49][50][51][52]. Thus, reliable, quantitative measures of ventricular performance may aid in the detection of MS in AB and to establish a better understanding of disease severity.…”
Section: Myocardial Dysfunctionmentioning
confidence: 99%
“…The LV ejection fraction (LVEF) is the most commonly used conventional parameter to quantify global LV systolic function in children with KD; however, previous studies have usually demonstrated normal LVEF in the acute phase [5,6]. Speckle tracking echocardiography (STE) has recently been shown to be a reliable method with which to assess LV systolic function and deformation through LV myocardial strain [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Although myocardial function and coronary artery diameter in most patients have recovered after treatment [6,8], there is evidence of ongoing myocardial and coronary arterial structural alterations in the long-term [11][12][13]. Few studies have focused on LV myocardial strain of children with a history of KD after long-term follow-up using STE, especially children with KD but without CAD [7][8][9]. Excluding coronary artery aneurysms, whether or not there is a long-term effect of CAD on LV myocardial strain is unclear.…”
Section: Introductionmentioning
confidence: 99%